História da ciência na Universidade de Coimbra - Carlota Simões (Documentos, 2013)
This book brings together a series of short texts by researchers on the History of Science project at the University of Coimbra, with the support of the Foundation for Science and Technology. It offers an overview of the Faculties of Mathematics and Philosophy from 1772 to 1933, with particular attention to the scientific literature published by the Coimbra University Press in the 18th and 19th centuries. It also contains an index of the 18th century scientific collections in Physics, Chemistry and Natural History, kept in the University Science Museum; a history of the Anthropology collections in the same museum; a text about the Faculty of Medicine in the 19th century, which deals with its relationship with the Faculties of Mathematics and Philosophy; a description of the Office of Geometry at the Faculty of Sciences, created in 1911; and finally a text about the history of the Science Class at the Coimbra Institute, the academy that functioned as an extension of the University.